Hubungan Antara Self-Efficacy dengan Pengambilan Keputusan Karier pada Mahasiswa Tingkat Akhir Fakultas Psikologi: (Studi Kasus Pada Universitas Di Jakarta Barat) - Ruth Imelda Kurniasari; Agoes Dariyo; Rita Markus Idulfilastri (Universitas Islam Tribakti Lirboyo Kediri, 2018)
Bandura (1997) says that self-efficacy is an individual's belief in his ability that affects the individual's way of reacting to certain situations and conditions. According to Gati, Krausz and Osipow (1996) suggested career decision-making refers to